E2F1 Induces KIF26A Transcription and Promotes Cell Cycle Progression via CDK–RB–E2Fs Feedback Loop in Breast Cancer - Xu, Jing; Liu, Lei; Ma, Ranran; Wang, Yawen; Chen, Xu; Liu, Haiting; Ji, Youxin; Liu, Tiantian; Gao, Peng (Frontiers in Oncology, 2021)
Objective: The aim of this study was to investigate the role of KIF26A in breast cancer. Method: qRT-PCR and immunohistochemistry were conducted to explore KIF26A expression and functional contribution to breast cancer development. MTS, EDU, colone formation assays, and flow cytometry analysis were conducted to assess cell proliferation characteristics and cell cycle progression. A series of 5’-flanking region deletion plasmids and mutating the binding site, with the luciferase reporter assay, were used to identify the core promotor region of KIF26A. The prediction by software and construction of the transcriptional factor plasmids were used to identify the transcriptional factor. Chromatin immunoprecipitation assay could demonstrate transcriptional factor directly binding to the KIF26A promoter. Human Genome Oligo Microarray Assay and gene ontology (GO) and pathway analyses were used to predict the downstream pathway. Results: Our results showed that in breast cancer tissues, elevated KIF26A expression was significantly correlated with lymph node metastasis. KIF26A could promote proliferation and G0/G1 phase cell cycle progression in breast cancer cells. The core promoter region of the human KIF26A gene was located upstream of the transcription start site at position -395 to -385. The transcriptional factor E2F1 was shown to activate KIF26A expression. Furthermore, KIF26A was shown to inhibit the expression of p21, then activate CDK-RB-E2Fs pathway. The elevated E2F1 can activate the cell cycle progression and the KIF26A expression, forming feedback loop. Conclusions: The present study demonstrated that KIF26A, directly upregulated by E2F1, promoted cell proliferation and cell cycle progression via CDK-RB-E2Fs feedback loop in breast cancer.